Case Report: Disseminated Mycobacterium intracellulare Infection With More Than 1-Year Follow-Up in a Young Boy With IFNGR1 Deficiency - Jia, Jihang; Zhu, Yu; Guo, Qin; Wan, Chaomin (Frontiers in Pediatrics, 2022)
All members of the genus Mycobacterium are collectively labeled as “non-tuberculous mycobacterium” (NTM), with the exception of the Mycobacterium tuberculosis complex and M. leprae. Recently, the incidence of NTM infection and number of cases have been increasing, but their identification remains difficult in some countries. Usually, NTM infections and diseases are associated with primary immunodeficiency diseases (PIDs), and their prognoses can be improved with a timely diagnosis and appropriate treatment. Here, we report a case of a 3-year-old boy with disseminated NTM disease (Mycobacterium intracellulare) and interferon-γ receptor 1 (IFNGR1) deficiency. He presented with skin and soft-tissue disease, disseminated osteomyelitis, and pulmonary disease. Initially, we suspected an infection due to the Bacillus Calmette–Guérin vaccine but later suspected Langerhans cell histiocytosis. Following oral treatment of azithromycin, rifampicin, and ethambutol, his condition improved progressively according to clinical and imaging manifestations. This case highlights the importance of early identification of the pathogen in a timely prescription of specific treatments in PIDs patients. We also discuss our experience of treatment of M. intracellulare disease in patients with IFNGR1 deficiency.